2013
DOI: 10.1039/c3cc43947j
|View full text |Cite
|
Sign up to set email alerts
|

Direct 2-acetoxylation of quinoline N-oxides via copper catalyzed C–H bond activation

Abstract: An efficient and direct 2-acetoxylation of quinoline N-oxides via copper(I) catalyzed C-H bond activation has been developed. This transformation was achieved using TBHP as an oxidant in the cross-dehydrogenative coupling (CDC) reaction of quinoline N-oxides with aldehydes, and provided a practical pathway to 2-acyloxyl quinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…It was found that switching the copper salt from CuBr to the more Lewis acidic CuOTf increased the yield from 69 % to 77 %. The solvent plays a crucial role in allowing better yields and shorter reaction times (Scheme ) …”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…It was found that switching the copper salt from CuBr to the more Lewis acidic CuOTf increased the yield from 69 % to 77 %. The solvent plays a crucial role in allowing better yields and shorter reaction times (Scheme ) …”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…[49] A broad range of electron-donor aryl aldehydes and cyclohexyl aldehyde work well under the standard conditions. [49] A broad range of electron-donor aryl aldehydes and cyclohexyl aldehyde work well under the standard conditions.…”
Section: Acyloxylation Of N-oxidesmentioning
confidence: 99%
“…Amongst them, the most notable development has been in the area of direct C−H functionalization of readily accessible quinoline‐ N ‐oxides where the N ‐oxide linkage primarily acts as a directing group (DG) which can be either easily removed or can act as a traceless DG. Over the recent past, transition metal‐catalysed alkenylation, arylation, alkynylation, phosphonylation, sulfonylation, acetoxylation and amidation have been reported directly at the C‐2 position of quinoline‐ N ‐oxides. In addition to C‐2 position, C−H activation at a distal C‐8 position of quinoline‐ N ‐oxides is also feasible however examples of such transformations are scarce in comparison to C‐2 functionalization.…”
Section: Introductionmentioning
confidence: 99%